Cryptic diversity and virulence of Beauveria bassiana recovered from Lycorma delicatula (spotted lanternfly) in eastern Pennsylvania - Clifton, Eric H.; Castrillo, Louela A.; Jaronski, Stefan T.; Hajek, Ann E. (Frontiers in Insect Science, 2023)
The entomopathogenic fungus Beauveria bassiana is cosmopolitan and known to infect a variety of sap-sucking pests like aphids, mealybugs, and scales in the order of Hemiptera. In Fall 2017, spotted lanternfly (SLF) adults killed by the fungal entomopathogen Beauveria bassiana were found in Berks County, Pennsylvania. In 2018-2020 we collected SLF and nearby non-target insects killed by Beauveria spp. from 18 field sites in southeastern Pennsylvania. We identified 159 Beauveria isolates from SLF and six isolates from non-targets. Five isolates of B. bassiana and one isolate of Beauveria brongniartii were identified from the non-targets. Based on sequence data from the nuclear B locus (Bloc) intergenic region, all the isolates from SLF were identified as B. bassiana, but there were 20 different strains within this species, grouped into two clades. Three B. bassiana strains (A, B, and L) were found in most field sites and were the most prevalent. Representative isolates for these three strains were used in laboratory bioassays and were compared to a commercial B. bassiana strain (GHA). Strain B was inferior to A, L, and GHA against nymphs; strains A and L had greater efficacy than B and GHA against adults. We also quantified conidial production on SLF cadavers. This paper discusses the diversity of these B. bassiana strains in SLF populations and implications for biological control of this abundant invasive.